Characterization of a fluorescence imaging probe that exploits metabolic dependency of ovarian clear cell carcinoma - Saki Tsuchimochi; Osamu Wada-Hiraike; Yasuteru Urano; Asako Kukita; Kohei Yamaguchi; Harunori Honjo; Ayumi Taguchi; Michihiro Tanikawa; Kenbun Sone; Mayuyo Mori-Uchino; Tetsushi Tsuruga; Katsutoshi Oda; et al. (Scientific Reports, 2023)
Abstract The purpose of this study is to clarify the metabolic dependence of ovarian clear cell carcinoma (CCC) by comparing normal tissues and to examine the applicability of fluorescence imaging probe to exploit these metabolic differences. Enhanced glutathione synthesis was supported by the increased uptake of related metabolites and elevated expression levels of genes. Accumulation of intracellular iron and lipid peroxide, induction of cell death by inhibition of the glutathione synthesis pathway indicated that ferroptosis was induced. The activation of γ-glutamyl hydroxymethyl rhodamine green (gGlu-HMRG), a fluorescent imaging probe that recognizes γ-glutamyl transferase, which is essential for the synthesis of glutathione, was investigated in fresh-frozen surgical specimens. gGlu-HMRG detected extremely strong fluorescent signals in the tumor lesions of CCC patients, compared to normal ovaries or endometrium. These results revealed that CCC occurs in the stressful and unique environment of free radical-rich endometrioma, and that glutathione metabolism is enhanced as an adaptation to oxidative stress. Furthermore, a modality that exploits these metabolic differences would be useful for distinguishing between CCC and normal tissues.